The nurse and the practices of assistance for the client politraumatized in emergency sector - Silva, Felipe do Cabo; da Silva, Roberto Carlos Lyra (Revista de Enfermagem UFPE on line, 2009)
Objective: to identify the main technical difficulties operational faced by the nurse in the sector of politrauma during the assistance for the client politraumatized. Methods: this is about a descriptive study, from qualitative approach, performed with 10 nurses from politraumatized sector at large public hospital in Rio de Janeiro city, Brazil, from July to August 2007. Information was collected through structured interviews script whose analysis was based on content analysis, thematic analysis, method proposed by Bardin. Results: through the testimonies if realizes to real situation of public service emergency from Rio de Janeiro city. When evaluating the assistance provided to the client politraumatized, we note several technical problems operational what make difficult the nurse work with these clients. Conclusion: the emergency care of trauma victims to the customer still needs many improvements. The technology, when put into practice the correct way, become a facilitator, minimizing the difficulties, contributing to the development of technical and scientific professionals and increasing the survival of the client polytraumatized in serious condition. Descriptors: politraumatized; emergency; nursing care.